Religiosity: Mediator of Tax Knowledge and Tax Compliance among Small Business Enterprises (SBEs) - Francis Tamale; Violah Mpangwire; Laura A. Orobia; Benjamin Musiita; Thomas Kisaalita; Brian Ssembatya; Kalimu Ndaazano; Brenda Kabasinguzi; Richard Mwesige (Technology and Investiment, 2025)
This study uses data from small business enterprises (SBEs) in a developing African economy to investigate the role of mediating religiosity in the link between tax Knowledge and tax compliance. This study used closed-ended questionnaires and a quantitative research design. This study employed a cross-sectional and correlational approach. A total of 283 SBE managers provided usable questionnaires, and SPSS v23 and the MedGraph application (Excel version) were used to analyze the data. Religion acts as a partial mediating factor in the relationship between tax compliance and tax knowledge. The results also indicate a strong relationship between tax compliance, tax awareness, and religiosity. Only one methodological research procedure was used, and triangulation may be attempted in future interviews. Furthermore, the results of this study were cross-sectional. More research should be conducted to assess the mediating effects examined in this study over time. A valid interpretation of the correlations between research variables always requires an analysis of the involvement of a third variable (religiosity) in the connection. This enables specialists and researchers to comprehend and reach valid conclusions and selections that might aid in improving tax compliance. Despite the abundance of research on tax compliance, this study uses SBE findings from Uganda, a developing economy in Africa, to provide the first empirical evidence of the mediating role of religiosity in the relationship between tax awareness and tax compliance.
Keywords: Uganda; Tax Compliance; Tax Knowledge; Religiosity; Small Businesses